How blockchain will change organizations - Tapscott, Don (MIT Sloan Management Review, 2016)
Blockchain technology has the potential to transform how businesses are organized and managed. It allows companies to eliminate transaction costs and use outside resources as easily as internal resources. The implications for areas such as accounting, contract negotiation and enforcement, sales and marketing, and capital investment are myriad. Companies should start exploring how this technology could impact their industry and processes.